“Wong Kemisan, Ngalap Barokah”Beggers In The Narrative of Alms Paku Buwono X Year 1893-1939 - Carlina, Resianita; Kusairi, Latif (Universitas Negeri Semarang, 2024)
This research explains the history of beggars in Surakarta. This topic selection was motivated by the scarcity of written studies discussing these events in local history as well as undisclosed primary sources. The problem in this research is how the history of beggars in the narrative of alms Paku Buwono X. In this thesis research, the author collects and compiles data through library research in the form of archives, books, journals, newspapers, articles, websites related to this research. The results of this study indicate that the mention of the term beggar originated from alms on Thursday by the tenth king of the Surakarta Sunanate. On Thursday, Paku Buwono X will leave the palace to see the condition of his people and give udhik-udhik to his people who are neatly lined up along the road with his hands raised. Paku Buwono X is a generous king, on Thursday Paku Buwono X will tour several places inhabited by poor people who expect from other people's gifts. The mention of the term beggar originated from the activity of giving alms on Thursday by the tenth king of the Surakarta Sunanate. On Thursday, Paku Buwono X will leave the palace to see the condition of his people and give udhik-udhik to his people who are neatly lined up along the road with his hands raised.In the Malay dictionary in 1939 there is the word kemis = day, which then becomes the word begging, begging, begging, starting from the word kemis which means Thursday, begging which means wishing for blessings on Thursday, begging by raising your hand, begging and being the beggar we know today.